AN EVALUATION OF A SCHOOL SYSTEM'S EFFORT TO DEVELOP AND IMPLEMENT A LEADERSHIP PREPARATION PROGRAM - Miller, Wendy (East Carolina University, 2015)
This study is a program evaluation of one school system’s effort to develop and implement a leadership preparation program. The study was designed to determine if the implementation of the GROW program addressed the problem of the lack of qualified and interested leadership candidates currently within the district. Data were gathered to determine if the completers of the district-designed GROW program had an increased level of interest in securing school leadership positions. The framework for the study was based on Donald Kirkpatrick's (2006) Model of Program Evaluation and included four levels of evaluation: (1) reaction, (2) learning, (3) behavior, and (4) overall results of the program. Quantitative and qualitative evaluation methods used in the study included surveys, questionnaires, pre and post assessments, and individual interviews. The findings of the study indicate that the GROW program was effective for participants and beneficial to the school district. GROW participants reported a high level of satisfaction with the program and felt better prepared for school leadership positions. The research revealed emergent themes that supported participant growth in key leadership principles. The research also supported the value of the cohort model, the powerful influence of “tapping”, and advantages of a district run program as compared to university programs. Ninety-five percent of GROW program participants reported an increased level of interest in school leadership. The GROW program was perceived as effective in increasing the number of interested and qualified candidates for school leadership positions in the host district. Further, preliminary data from this study was used in a grant proposal to the Z. Smith Reynolds Foundation seeking funding support for leadership initiatives in Craven County Schools. The grant was awarded in the amount of ninety thousand dollars. The results of this study have impacted the future of leadership initiatives in Craven County Schools.
Keywords: Leadership development; Grow your own leaders; Teachers--In-service training--North Carolina--Craven County; School administrators--North Carolina--Craven County; Educational leadership--North Carolina--Craven County; School personnel management--North Carolina--Craven County; Craven County Schools